Perbandingan Hasil Belajar Model Number Head Together, Jigsaw,Picture and Picture, Group Investigation. - Riana Yunisa; Tedi Rusman; Rahmah Dianti Putri; I Komang Winatha (JEE (Jurnal Edukasi Ekobis), 2019)
This study aims to determine the comparison of economic learning outcomes using the Number Head Together, Jigsaw, Picture and Picture learning models and group investigation. The method used in this research is descriptive method with a comparative approach. The population in this study amounted to 53 respondents. The sample obtained was 53 respondents. Data collection is done through observation, interviews, and tests. Hypothesis testing uses the two-way variance analysis formula and two independent sample t-tests. The analysis shows that there is a comparison of economic learning outcomes using the number head together, jigsaw, picture and picture learning model, and group investigation.Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar ekonomi menggunakan model pembelajaran Number Head Together, Jigsaw, Picture and Picture dan group investigation. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan komparatif. Populasi dalam penelitian ini berjumlah 53 responden. Sampel yang diperoleh adalah 53 responden. Pengumpulan data dilakukan melalui observasi, wawancara, dan tes. pengujian hipotesis menggunakan rumus analisis varian dua jalan dan t-test dua sampel independen. Hasil analisis menunjukkan bahwa ada perbandingan hasil belajar ekonomi dengan menggunakan model pembelajaran number head together, jigsaw, picture and picture, dan group investigation.Kata Kunci : Number Head Together, Jigsaw, Picture and picture, Group Investigation, Hasil Belajar Ekonomi